ADOPTING STRATEGIC MANAGEMENT IN PLANNING AND IMPLEMENTATION OF ENTREPRENEURSHIP EDUCATION IN TERTIARY INSTITUTIONS IN NIGERIA - Gbandi Eleazar Chibuzor; Eboreime Ohimai Friday (European Scientific Journal, ESJ, 2013)
Entrepreneurship education is the acquisition of knowledge, skills and attitude to enable the learner apprehend life challenges in whatever form and take decisive steps to realize new trends and opportunities for meeting those challenges in all aspects of human life. This paper discussed entrepreneurship education that is in consonant with the prevailing contemporary global and local environment. This could be successfully achieved through the adoption of strategic management in setting the objectives, planning, implementation and evaluation of entrepreneurship education programmes in Nigeria. This will enable the students fit into a comprehensive entrepreneurship education programmes according to their interest and passion with the prevailing opportunities provided by the environment. Such programmes will not only provide theoretical knowledge but will also ensure that graduates develop an entrepreneurial mindset, through developing entrepreneurial skills, behaviours and attitudes that will equipped them with the key competencies to enable them enjoy an entrepreneurial /intrapreneurial career or engage in new venture creation.